Evaluation of tree species using Air Pollution Tolerance Index for urban landscaping in Delhi - SINGH, LOKENDRA; SINDHU, SATBIR SINGH; SINGH, MAM CHAND; JAISWAL, SARIKA; ANKIT; KUMAR, SUDHIR; SHARMA, DINESH KUMAR; SINGH, BABITA; ANAND (The Indian Journal of Agricultural Sciences, 2024)
Air pollution which negatively impacts both human health and the environment is a mountainous challenge before policymakers and city planners in urban areas. Urban landscaping with effective pollution-combating tree species is one of the soundest strategies to mitigate pollution adversaries. However, not all tree species are equally suitable for urban environments due to varying levels of tolerance to air pollution. This study has been designed to evaluate the physiological and biochemical responses of seven commonly occurring tree species in the Talkatora garden (TG) and Income Tax Office (ITO) representing non-polluted and polluted locations in Delhi, respectively applying Air Pollution Tolerance Index (APTI). The current research study was carried out during 2021–22 at the Division of Floriculture and Landscaping, ICAR-Indian Agricultural Research Institute, New Delhi. In tree species understudy, it was recorded that the pH of leaf extract, total chlorophyll, and relative water content was lower in the winter season than summer season except for the ascorbic acid. Ficus religiosa with the highest APTI value (23.23) followed by Pongamia pinnata (20.85) were found most tolerant tree species to air pollution in Delhi during the winter season at the polluted (ITO) and non-polluted (TG) location respectively with a reverse trend for the summer season. Polyalthia longifolia was found most sensitive (bioindicator plant) to air pollution among the seven trees under study owing to the lowest APTI values (11.14 and 12.58) across the seasons at non-polluted (TG) and polluted (ITO) locations respectively. Furthermore, Ficus religiosa with the highest APTI across the locations and seasons was assessed as the best performer, hence, could be the most efficient option for landscaping in polluted and non-polluted areas.